Crowdsourcing as production model that uses collective intelligence, the collaborative culture and the formation of communities - Luciano Augusto Toledo; Felix Hugo Aguero Diaz Leon (Innovation & Management Review, 2019)
Purpose - It has been verified that companies are using crowdsourcing to carry out tasks related with the market, concentrating on three main areas: product development, advertising and promotion and market research. This study aims to carry out qualitative research using the case study method. The analysis unit that will be used will be marketing activities based on crowdsourcing. Finally, the study subjects used to understand the phenomenon are Coca Cola, PepsiCo, Netflix and Amazon. Design/methodology/approach For this study, the decision was made to use the case study method due to its qualitative character. Thus, the analysis unit of the study is composed of the activities of the company investigated related to the activities of the marketing information system. For this study, a unique case study was used. The object companies were Coca Cola, PepsiCo, Netflix and Amazon. Findings A significant number of advantages are therefore perceived for companies that adopt mass collaboration practices in the research and development of products. The strategic importance of this concept for companies that launch themselves into these surprising endeavors is ever more clear and consolidated in their planning. It is up to those sectors that are responsible for communication to think of strategies that incorporate the collaborative work of consumers into their actions. Research limitations/implications The study presents some limitations that give rise to the opportunity to embark on future studies. As it is an exploratory study, there was no validation of causality between variables, which may diminish the empirical value of the findings. In this context, the sample is small and non-probabilistic, which on one hand made applying the interviews in the field study viable, but on the other does not enable the results to be generalized. Practical implications The transfer of power to crowds of consumers has led to a reduction in costs. This combination of innovative and cost reduction constitutes value innovation, a basic factor for customer retention, standing apart from the competition and obtaining appreciable results, thus reducing mortality. Social implications A collaborative action is an integrated marketing and communication action. In the same way, using bloggers to evaluate products today is a basic form of research and development, networking and communication with consumers, who become co-creators of products and services, as well as interlocutors with those responsible for corporate communication. Originality/value A significant number of advantages are therefore perceived for companies that adopt mass collaboration practices in the research and development of products. The strategic importance of this concept for companies that launch themselves into these surprising endeavors is even more clear and consolidated in their planning. It is up to those sectors that are responsible for communication to think of strategies that incorporate the collaborative work of consumers into their actions.
Keywords: 650; Marketing; Crowdsourcing; Strategy